TaSPoD® - Rafiza, A.R.; Aizal Yusrina, I. (University of Malaya, 2014)
Training System for Professional Development (TaSPoD) is an online training system for educators in the higher learning institutions in Saudi Arabia. The main purpose of the system is to enhance and equip educators competency, professionalisms, knowledge, skills and practices in an effective way; utilizing the system through appropriate electronic devices that are connected to the Internet. TaSPoD offers educators the opportunity of asynchronous or self-paced training process. The online system is basically divided into 3 distinct components; the training module, the assessment module and the management module. This trademark registered in class 9, 16, 35, 38, 41, and 42.